USING THE THINK-PAIR-SHARE STRATEGY IN TEACHING READING NARRATIVE TEXT FOR JUNIOR HIGH SCHOOL STUDENTS - Yolanda Ageasta; Witri Oktavia (Universitas Negeri Padang, 2018)
Based on the writer’s experience, many students have not interested in reading text, they do not have motivation in reading and the students become passive in the class. Considering such problem, an appropriate strategy in teaching is needed to help students to improve their ability in reading. This paper aims at explaining how to implement think-pair-share strategy in reading narrative text. Think-pair-share strategy conducted students to do three phases. The students have “wait time” go review their background knowledge about the topic. Then the teacher divides the students to work in pair after answer the question individually. After that, each of students shares their answer and ideas in pair. Finally, the students present their discussion in front of the class individually. The objective of this paper is to help the students visualize their knowledge in the form of group work and improve student motivation and ability in reading narrative text.